(untitled) (Research, Society and Development, 2024)
Objective: To analyze and gather information to understand the role of nursing in the assessment and management of cancer pain in order to highlight the importance of nursing care for promoting the quality of life of cancer patients. Methodology: This is a descriptive, qualitative study, of the Integrative Literature Review type, and the databases Medical Literature Analysis and Retrievel System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS) were used through the Virtual Health Library (VHL). Regarding the Health Science Descriptors (DECS/MESH), the following were used: Nursing Care; Nursing; Pain Management and Cancer Pain, in Portuguese, English and Spanish. Results and Discussion: 6 articles were included to make up the scope of this review. During the study, it was possible to verify that there is a lack of knowledge among nurses regarding the use of opioids to control pain in cancer patients. Likewise, according to the studies analyzed, they have inadequate knowledge of the topic, therefore there is an urgent need for constant improvement. Final Considerations: According to the studies analyzed, it is concluded that pain in cancer patients should be treated with the same importance as other symptoms considered serious. To this end, it is important that nurses empower themselves with the knowledge to appropriately manage pain, using scales for its assessment, and know the appropriate time and way to intervene in each case.